2003
DOI: 10.1021/jf030332y
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Natamycin:Cyclodextrin Inclusion Complexes and Their Characterization

Abstract: Natamycin is a broad spectrum antimycotic with very low water solubility, which is used to extend the shelf life of shredded cheese products. beta-Cyclodextrin (beta-CD), hydroxypropyl beta-cyclodextrin (HP beta-CD), and gamma-cyclodextrin (gamma-CD) were found to form inclusion complexes with natamycin in aqueous solution. The increase in solubility of natamycin with added beta-CD was observed to be linear (type A(L) phase solubility diagram). The 1:1 stability constant of natamycin:beta-CD complex was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 22 publications
7
41
0
Order By: Relevance
“…It has been reported that the inclusion complexes of guest compounds with CDs can enhance guest stability, improve the aqueous solubility, protect against oxidation, light-induced decomposition, and heat-induced changes, and mask or reduce unwanted physiological effects, and reduce volatility (Hedges, 1998). For example, the natamycin/CDs complexes have allowed a homogeneous delivery system of natamycin to the shredded cheese surface without the clogging of spray nozzles during cheese production (Koontz & Marcy, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the inclusion complexes of guest compounds with CDs can enhance guest stability, improve the aqueous solubility, protect against oxidation, light-induced decomposition, and heat-induced changes, and mask or reduce unwanted physiological effects, and reduce volatility (Hedges, 1998). For example, the natamycin/CDs complexes have allowed a homogeneous delivery system of natamycin to the shredded cheese surface without the clogging of spray nozzles during cheese production (Koontz & Marcy, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The cyclodextrin molecule can at least partially shield the guest molecule from degradation caused by light, oxidation, heat, and acidic or alkaline conditions [9]. Cyclodextrins not only insulate labile compounds from a potentially corrosive environment, they also increase solubility of poorly soluble agents [8,10]. Inclusion of natamycin into cyclodextrin permits the preparation of a complex containing 500 mg/L of solubilised natamycin and protects natamycin from inactivation in an acidic environment as prevailing in beverages.…”
Section: Pharmacology Of Natamycinmentioning
confidence: 99%
“…Natamycin, as a natural preservative, is used in dairy products and other foods in over sixty countries (Delves-Broughton et al, 2005). Natamycin is identified by the European Union as a natural preservative (EFSA, 2009) and it has been described as generally recognized as safe (GRAS) product for human by FDA (Koontz and Marcy 2003).…”
Section: Introductionmentioning
confidence: 99%